Protection Motivation Theory (PMT) Teori dan Aplikasi - Mustika Fatimah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Health is a basic human need as described in Law No. 36 of 2009, which is considered physically, mentally, and socially that enables everyone to live productively. One indicator that reflects health in the community is the health behavior carried out by individuals in the community itself. Protection Motivation Theory (PMT) is an approach model that can be used to predict a person's healthy behavior. This research is a literature study that aims to explain the theory and various forms of PMT applications. The PMT consists of a threat appraisal that is individualized based on disease susceptibility and perceived severity. The way an individual chooses to respond to a threatening situation is based on two beliefs, namely 1) implementing a behavior that will resolve the threat (response efficacy) and 2) the individual's belief about his or her ability to perform the behavior effectively (self-efficacy). Fear will elicit an adaptive response (intention to perform a behavior) or a maladaptive response (avoidance or rejection). The PMT framework is used to explain healthy human behavior where it is fear that is used to control or change a person's behavior. PMT applications can be used not only in the health sector but also in other fields. PMT application is not only used to identify behavior but also for maladaptive behavior intervention.